Implementation of Small Group Discussion Method as an Effort to Improve Student Learning Outcomes in English Subjects for Junior High School (Journal Intellectual Sufism Research (JISR), 2023)
This research is classroom action research with two ( II) cycles which aims to determine the improvement in learning outcomes and responses of class IX-B students at SMP Negeri 21 Surabaya in learning the material. Agreement and Disagreement through models Small Group Discussio n . Data collection methods include observation, questionnaires and tests . Subject study is participant educate class IX-B SMPN 21 Surabaya Academic Year 2023/2024. Object study is enhancement results learn and respond students on the material Agreement and Disagreement through models Small Group Discussion. Research result showing that in cycle I the percentage completeness Study student reached 64% and rising to 88% in cycle II. Response student to application method Small Group Discussion showing positive response . _ Therefore can concluded that application method small group discussions can increase  learning outcomes and student responses _ significant to the eye Middle School English lessons This research is classroom action research with two ( II) cycles which aims to determine the improvement in learning outcomes and responses of class IX-B students at SMP Negeri 21 Surabaya in learning the material. Agreement and Disagreement through models Small Group Discussio n . Data collection methods include observation, questionnaires and tests . Subject study is participant educate class IX-B SMPN 21 Surabaya Academic Year 2023/2024. Object study is enhancement results learn and respond students on the material Agreement and Disagreement through models Small Group Discussion. Research result showing that in cycle I the percentage completeness Study student reached 64% and rising to 88% in cycle II. Response student to application method Small Group Discussion showing positive response . Therefore can concluded that application method small group discussions can increase  learning outcomes and student responses significant to the eye Middle School English lessons
Keywords: English subject; small group discussion; learning outcomes